(untitled) (Jurnal Abdimas Administrasi Kesehatan, 2021)
Hospitals as health service institutions must provide services to the community in the local and international scope. Based on this, in the last few decades, the term accreditation has emerged to assess the quality of an organization including hospitals. Hospital accreditation is linked to quality assessment. However, actually quality itself is an outcome of implementing accreditation, while accreditation only assesses that the service has met the standard or not without measuring the quality of service. This community service was carried out from January 27 to 29, 2021 at RSIA. Jimmy Medika Borneo. The data collection method uses percentages and questions and answers to 100 respondents. Socialization of hospital accreditation to health students and hospital staff to community participants and health workers is categorized as running well and smoothly